THE IMPLEMENTATION OF MULTICULTURAL EDUCATION THROUGH ISLAMIC EDUCATION AT SCHOOL/MADRASAH - Saiful Bahri; Firdaus Syah; Munzir Munzir (Proceeding International Seminar of Islamic Studies, 2022)
Multiculturalism, a concept that must be emphasized in the life of the nation and state that directs mutual respect, respect for fellow human beings is none other than to live peacefully, Indonesia as the most extensive country with the majority of Muslims besides Christianity, Hinduism, Buddhism and Confucianism, multiculturalism which refers to the level of the concept of equality in social life that does not blame each other, slander and even spread hatred among others resulting in the loss of property and life, this concept must be instilled in the generation from the start, whether formulated in the educational curriculum, the material taught and the methods which is used as a manifestation of a generation that lives with tolerance, prioritizes dialogue or deliberation, helps each other to help each other.Keywords: Islamic Education, Multicultural, school